ANALISIS PENGELOLAAN KEUANGAN KELUARGA DALAM PERSPEKTIF EKONOMI ISLAM (STUDI TERHADAP KELUARGA PENERIMA DANA GANTI RUGI BENDUNG SEI WAMPU LANGKAT): Pascasarjana Universitas Islam Negeri (UIN) Sumatera Utara dan Sekolah Tinggi Agama Islam Negeri (STAIN) Mandailing Natal - KHAIRINA DAN SATRIA DARMA (Program Studi Perbankan Syariah Jurusan Syariah, Ekonomi dan Bisnis Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal (STAIN MADINA), 2020)
Abstract Family financial management is done to manage finances obtained from income received. The family income in this study is from the compensation of Sei Wampu Dam in Stabat District, Langkat Regency. The purpose of this study was to analyze, financial management of family financial management in an Islamic economic perspective (study of families of beneficiaries of dam damages) and constraints, factors and family models in managing compensation. The subject of this study was for Muslim families who received compensation funds for the sei wampu dam in Stabat District, Langkat Regency. This research is a field research using a qualitative approach. Based on the field review of the five families of compensation recipients there were differences in economic health conditions, it was found that three families had conditions that were not fully healthy because they did not have savings and insurance, but this family had investments, one family had savings and investment but no insurance , and finally one family has a healthy economic condition because it has savings, insurance and investment. This difference in economic conditions is motivated by differences in attitude in managing compensation money received. Factors that influence the family in managing compensation are: first, religious factors, second, cultural / traditional factors, third, lifestyle factors, fourth, education factors. As for the constraints of the recipient family in managing compensation received: First, do not have a reserve fund, Second, Not compact in managing finance, Third, Poor financial planning, Fourth, Difficulty in controlling self-restraint, Fifth, Heavy in saving, and Sixth , Does not record income and expenses. Keywords: Management of Family Finance, Compensation and Islamic Economy.